Telemetric hemodynamic assessment during anesthesia induction with propofol in experimental heart failure. Issue 2 (2021) - Vogel, Julia; Boehme, Philip; Wakili, Reza; Boden, Katharina; Reimer, Thomas; Sandner, Peter
No abstract available